2017
DOI: 10.1093/cercor/bhx206
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Auditory-Evoked Responses in Preterm Neonates: Revisited by Spectral and Temporal Analyses

Abstract: Characteristic preterm EEG patterns of "Delta-brushes" (DBs) have been reported in the temporal cortex following auditory stimuli, but their spatio-temporal dynamics remains elusive. Using 32-electrode EEG recordings and co-registration of electrodes' position to 3D-MRI of age-matched neonates, we explored the cortical auditory-evoked responses (AERs) after 'click' stimuli in 30 healthy neonates aged 30-38 post-menstrual weeks (PMW). (1) We visually identified auditory-evoked DBs within AERs in all the babies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 93 publications
4
23
0
Order By: Relevance
“…In line with our previous results (Routier et al, 2017), click stimuli similar to those used to evoke delta-brush activities in preterm newborns before 35 wGA (Chipaux et al, 2013;Kaminska et al, 2017) did not evoke TTA-SW events between 24-27 wGA. TTA-SW events for both bursts and IBI were considered in this analysis.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In line with our previous results (Routier et al, 2017), click stimuli similar to those used to evoke delta-brush activities in preterm newborns before 35 wGA (Chipaux et al, 2013;Kaminska et al, 2017) did not evoke TTA-SW events between 24-27 wGA. TTA-SW events for both bursts and IBI were considered in this analysis.…”
supporting
confidence: 91%
“…This observation holds in adults (Chacko et al, 2018;Helfrich, Mander, Jagust, Knight, & Walker, 2018;Mak-McCully et al, 2017;Mölle, Bergmann, Marshall, & Born, 2011;Voytek et al, 2010), where intrinsic CFC constitutes a key feature of ongoing neural activity (Engel, Gerloff, Hilgetag, & Nolte, 2013;Hyafil, Giraud, Fontolan, & Gutkin, 2015), which in turn supposedly enhances combinatorial opportunities for encoding (Fell & Axmacher, 2011;Rasch & Born, 2013) and facilitates synaptic plasticity (Bergmann & Born, 2018;Buzsáki & Draguhn, 2004;Salimpour & Anderson, 2019). In the present work, we show that this generic mechanism is already in place early in the course of development, that is, before the onset of better-known development-related oscillatory activities such as spindle bursts (M. T. Colonnese & Phillips, 2018;Khazipov & Milh, 2018), delta brush (Kaminska et al, 2017) and neonatal prefrontal oscillations (Brockmann, Pöschel, Cichon, & Hanganu-Opatz, 2011).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Recent experimental findings have demonstrated distinct developmental changes in the cortical processing of afferent information (Bernhard, Kolmodin, & Meyerson, ; Luhmann & Khazipov, ), while prior human work has suggested significant developmental changes in the early responses of multiple sensory modalities (Ellingson, , ; Hrbek et al, ; Hrbek & Mareš, ; Kaminska et al, ; Whitehead, Papadelis, Laudiano‐Dray, Meek, & Fabrizi, ). In our study, we observed an expected decline in cSER amplitudes; however, we also found a perhaps unexpected lack of comparable change in the iSERs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings together are compatible with the idea that the prominent ipsilateral responses in the preterm primary sensory cortices are a developmentally transient phenomenon during the period when organization of the sensorimotor cortical networks is guided by sensory input (Inacio et al, ). The immature, bursting‐type sensory responses akin to SERs are known to arise from a complex network involving subplate‐cortex structures, they disappear after the age comparable to human neonatal period (Chipaux et al, ; Kaminska et al, ; Luhmann & Khazipov, ) and they will be replaced by the adult‐like intracortical responses (for a schematic drawing, see Vanhatalo and Lauronen ()). Hence, though we cannot pinpoint the exact cortical area generating the prominent iSERs observed in our study, we suggest that they represent organization of the bilateral sensorimotor cortical networks, a phenomenon specific for the preterm period.…”
Section: Discussionmentioning
confidence: 99%